2021
DOI: 10.3390/agriculture11020180
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Myco-Biocontrol Based Formulates on Yield, Physiology and Secondary Products of Organically Grown Basil

Abstract: The development of organic farming as a result of increasing consumer preference for organic food has led to the development and registration of new pest-control products for certified organic production. In this study, the effects of three biocontrol products containing spores and mycelium of Arthrobotrys oligospora—Artis®, Beauveria bassiana—Bora®, and Coniothyrium minitans—Öko-ni® were tested on four basil (Ocimum basilicum L.) cultivars: ‘Aromat de Buzau’, ‘Serafim’, ‘Macedon’ and ‘Cuisoare’. The applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…After 90 min of incubation, the samples were read on the spectrophotometer at 760 nm. The results were interpreted according to the calibration curve as gallic acid equivalents per gram of dry mass [37,38].…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…After 90 min of incubation, the samples were read on the spectrophotometer at 760 nm. The results were interpreted according to the calibration curve as gallic acid equivalents per gram of dry mass [37,38].…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…In addition, the treatment with Azotobacter chroococcum 76A indicated greater phytostimulation efficacy with higher significant values of sweet basil in root dry weight, rate of CO 2 net assimilation and photosynthetic efficiency that can be related to a better fitness of the plant. The colonization of roots by Trichoderma may enhance growth response due to the enhancement of carbohydrate metabolism, photosynthetic and respiratory rates [ 45 ], thus triggering the plants physiological processes that improve the photosynthesis rate and stomatal conductance [ 57 ]. Silletti et al noted that the photosynthetic rate was similarly higher in wheat when treated with Trichoderma or with Azotobacter [ 48 ], whereas the bacteria was found to release phytohormones that could stimulate photosynthesis in basil [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated how the use of microorganisms can influence the essential oil and phenolic components on basil. For instance, the inoculum of AMF improved the concentration of rosmarinic acid, chicoric acid and caffeic acid on 4 basil cultivars [ 70 ], growth and aroma volatiles (e.g., linalool) on sweet basil in heavy-metal-contaminated soil [ 44 ], plus the use of different commercial microbial bio-based products increased the percentage of different metabolites (e.g., caffeic acid) on different basil cultivars [ 57 ]. Moreover, our results indicate that the simultaneous application of Trichoderma afroharzianum T22 with Azotobacter chroococcum 76A induced a better modulation of phenolics metabolism when compared to the single applications of Trichoderma and Azotobacter , especially for rosmarinic and caffeic acid, as is in line with findings by Sabra et al [ 44 ] affirming that the dual application of beneficial fungi and its associated bacteria generated an enhancement of sweet basil nutraceutical value.…”
Section: Discussionmentioning
confidence: 99%
“…Total chlorophyll content was measured with CCM 200 (chlorophyll content meter), a non-destructive portable device produced by ADC Bioscientific Ltd., Hoddesdon, UK, which measures total chlorophyll and expresses it in CCI units (Chlorophyll Content Index) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The gas exchange parameters, photosynthesis, and transpiration were measured with a portable compact system LCI Bioscientific UK Ltd., with a Narrow Leaf Chamber, with an area of 5.8 cm 2 , between 9–10 a.m. [ 38 ].…”
Section: Methodsmentioning
confidence: 99%